Fine Structure and Composition of the Zoogloeal Matrix Surrounding Zoogloea ramigera - Friedman, Barry A. (1968)
The fingerlike projections, which have been considered to be characteristic of the genus Zoogloea, appear to consist of generally globular packets of cells, each surrounded by capsular matrix. The individual packets which surround Z. ramigera 115 cells appear to adhere one to another by intermeshed fibrils that measure 2 to 5 nm in diameter. The fibril polymer appears to be polyglucose that is susceptible to cellulase. The polymer resembles cellulose in several respects, with the exception that it is soluble in 1 n NaOH. Although Z. ramigera I-16-M does not possess an observable zoogloeal matrix when viewed under a light microscope, chemical data indicate that it does produce cellulase-susceptible polymer. Fibrils can be observed under the electron microscope, which are resistant to 1 n NaOH and may be cellulose. Less polymer fibrils are observed around isolate I-16-M cells than around isolate 115 cells; the inability to observe the I-16-M material as a zoogloeal matrix under light microscopy may be due to lack of sufficient amount of polymer.